Unusual interactions of benzodiazepine receptor antagonists. - Nutt, D; Cowen, P; Little, H (1982)
Two compounds have recently been described which act as potent benzodiazepine (BDZ) antagonists in vivo and which, in vitro, show high affinity and selectivity for the BDZ receptor of the mammalian central nervous system (CNS). One, ethyl β-carboline-3-carboxylate (β-CCE), was extracted from human urine and may be related to an endogenous ligand for the BDZ, receptor. It reverses the effects of BDZs in vivo and in vitro, but also has intrinsic activity, as it loweres the seizure threshold to drugs antagonistic to the action of γ-aminobutyric acid (GABA). The other compound, an imidazodiazepine (Ro 15-1788), which is also a potent and specific antagonist of BDZ binding in vivo and in vitro, blocked the sedative, hypnotic and anticonvulsant actions of conventional BDZs, without demonstrating any intrinsic activity. Because of the different profiles of action of these two BDZ 'antagonists', we have here investigated their interactions in two well established systems for assessing BDZ activity: seizure thresholds in vivo and the action of GABA on cervical sympathetic ganglia in vitro. We find that Ro 15-1788 not only opposes the actions of BDZs but also is an effective antagonist of β-CCE in both systems. At high doses it has BDZ-like activity, suggesting that it may be a partial agonist at the BDZ receptor site.